2020
DOI: 10.1021/acs.orglett.0c02494
|View full text |Cite
|
Sign up to set email alerts
|

3,6,13,16-Tetrasubstituted Porphycene: The Missing Link in Porphycene Chemistry

Abstract: We have introduced the first 3,6,13,16-tetrasubstituted porphycene as its tetramethoxy analogue. This substitution pattern is one of the most general patterns yet missing in this isomeric porphyrin chemistry. This porphycene exhibits intense fluorescence along with the ability to coordinate with divalent metal ions; in particular, it forms the first stable Zn­(II) complex among the tetrasubstituted porphycenes. Notably, the molecular structure of Zn1•Py displays supramolecular chirality.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

1
4
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
6

Relationship

4
2

Authors

Journals

citations
Cited by 8 publications
(5 citation statements)
references
References 43 publications
1
4
0
Order By: Relevance
“…17b Although several types of peripheral substitutions have been explored, the synthesis of 3,6,13,16substituted porphycenes eluded chemists for more than three decades, 1b,c until our recent report of 3,6,13,16-tetramethoxyporphycene. 18 As expected it provided a square type core and formed complexes with various metal ions, including Zn(II) that showed supramolecular chirality in the solid state. However, we could achieve its synthesis through reductive dehalogenation of 2,7,12,17-tetrachloro-3,6,13,16-tetramethoxyporphycene or more preferably by subjecting the dechlorination reaction upon its precursor dichlorodimethoxybipyrrole dialdehyde 19a to obtain 3,3 0 -dimethoxybipyrrole dicarbaldehyde and performing McMurry coupling upon it.…”
Section: Introductionsupporting
confidence: 58%
See 2 more Smart Citations
“…17b Although several types of peripheral substitutions have been explored, the synthesis of 3,6,13,16substituted porphycenes eluded chemists for more than three decades, 1b,c until our recent report of 3,6,13,16-tetramethoxyporphycene. 18 As expected it provided a square type core and formed complexes with various metal ions, including Zn(II) that showed supramolecular chirality in the solid state. However, we could achieve its synthesis through reductive dehalogenation of 2,7,12,17-tetrachloro-3,6,13,16-tetramethoxyporphycene or more preferably by subjecting the dechlorination reaction upon its precursor dichlorodimethoxybipyrrole dialdehyde 19a to obtain 3,3 0 -dimethoxybipyrrole dicarbaldehyde and performing McMurry coupling upon it.…”
Section: Introductionsupporting
confidence: 58%
“…17a However, Vogel found that the methyl substituents at the 2,7,12,17-positions impart greater structural deviations in the fused dibenzoporphycenes compared to the t-butyl groups. 22 Further, 1a displayed a square-type N4-core (N1-N2: 2.73 Å; N1-N4: 2.77 Å) like that found in the case of the tetramethoxy analogue 18 and the core was very similar to that of both etioporphycene and b-octaethylporphycene. 17a This clearly indicates that the outer b-substituents have minimal implications upon the structure of porphycenes, an attribute earlier reported upon exchange of methoxy with chloro groups at those positions.…”
Section: Single Crystal X-ray Diffraction Analysismentioning
confidence: 56%
See 1 more Smart Citation
“…This was clearly evident in type A and type B porphycenes having substituents at the meso - and outer-β-pyrrolic positions, respectively (Figure ), where coordination with metal ions was found to be difficult to perform. ,, Vogel found the presence of substituents at the 3,6,13,16-positions in β-octaalkylporphycenes reduced the strength of the NH···N hydrogen bond owing to nonbonding interactions, thereby making the macrocyclic core more of a square-type . After more than three decades, we recently synthesized the first 3,6,13,16-substituted porphycene (type C ), which was found to display slightly stronger NH···N hydrogen bonding than the type D analogues . Further, they are endowed with the best attributes of porphycenes in terms of their coordination chemistry and photophysical properties.…”
mentioning
confidence: 64%
“…13c After more than three decades, we recently synthesized the first 3,6,13,16-substituted porphycene (type C), which was found to display slightly stronger NH•••N hydrogen bonding than the type D analogues. 15 Further, they are endowed with the best attributes of porphycenes in terms of their coordination chemistry and photophysical properties.…”
mentioning
confidence: 99%